GC-MS And FTIR Analysis Of Endolichenic Fungus Penicillium Sp. Isolated From Cryptothecia Striata Of Arunachal Pradesh, India (International Journal of Food and Nutritional Sciences, 2022)
In the present study GC-MS and FTIR analysis of an endolichenic fungus Penicillium sp. isolated from Cryptothecia striata was done to identify the bioactive compounds present in it. Our study indicated the presence of may functional groups as identified through FTIR analysis and GC-MS analysis of methanolic extract of Penicillium sp.(CRP 3a) shows the presence of eight compounds such as Phenol 3,5-Bis(1-1 Dimethyl ether), Pentanoic acid,5-hydroxy-2,4-di-t-butyl phenyl esters, Pentanedioic acid,(2,4-Di-T-Butylphenyl ester) ,ethyl crysanthemate , Carissanol Dimethyl ether, Vanillin and Diethyl,2-6 –Pyridine- dicarboxylate. Some of the compounds exhibited strong antimicrobial activity and it has been hypothesized that the antimicrobial activity of lichen might be due to the associated endolichenic fungi.